The geometrical effect of different annuloplasty rings on mitral valve annulus - Maisary, Sameer al-; Graser, Bastian; Engelhardt, Sandy; Wolf, Ivo; Karck, Matthias; De Simone, Raffaele (The journal of cardiovascular surgery, 2017)
BACKGROUND: Different types of mitral annuloplasty rings are commercially available. The aim of this study was to investigate the effect of implantation of six types of annuloplasty rings on the geometry and dynamics of the mitral valve. METHODS: Three-dimensional echocardiography images of 42 patients were acquired to visualize the mitral valve annulus. Virtual representations of six commercially available annuloplasty rings were matched to anatomical mitral annuli of each patient according to anterolateral-posteromedial diameter. The virtual displacement of each annuloplasty ring after the implantation was measured and compared with the other rings. RESULTS: Patients with severe mitral regurgitation had significantly dilated annuli according to anterolateral-posteromedial diameter, anterior-posterior diameter and to annulus circumference. Anterior and posterior heights of the mitral annuli and non-planarity angle showed no significant differences among different patients with different degree of mitral regurgitation. The ratio of anterior-posterior to anterolateral-posteromedial diameter was almost identical in all groups with identical annular shapes. The implantation of the Carpentier-Edwards Classic Annuloplasty Ring™ led to maximal displacement of mitral annulus, followed by the IM-Ring™, without a statistical significance. In contrary, the implantation of a MyxoETlogix Ring™ was associated with minimal displacement of mitral annulus throughout the groups, but without statistical significance. CONCLUSIONS: The implantation of different ring types in patients with different annuli shapes and dimensions did not lead to any significant change in the configuration of mitral annuli after the virtual implantation of the tested annuloplasty rings.